Effect of application compost and vermicompost from market waste on soil chemical properties and plant growth - Syarifinnur Syarifinnur; Yulia Nuraini; Budi Prasetya (Journal of Degraded and Mining Lands Management, 2022)
This study was conducted to determine the effect of compost and vermicompost from market organic waste on the soil chemical properties and the growth of maize. The treatments tested were three doses of compost (2.5, 5, and 10 t/ha), three doses of vermicompost (2.5, 5, and 10 t/ha), and one control (without compost or vermicompost). At the time of harvest (10 weeks after planting), maize shoot dry weight, root dry weight, cob length, cob diameter, cob with husk, and cob dry weight, as well as the soil chemical properties organic carbon (C), total nitrogen (N), total phosphorus (P), available P, total potassium (K), and pH were observed. Maize plant height, leaf number, and stem diameter were observed at 2, 4, 6, and 8 weeks after planting. The results showed that the application of compost and vermicompost significantly affected soil chemical properties and the yield of maize. The application of 10 t vermicompost/ha resulted in the highest yield of maize and highest increase of soil organic carbon, total phosphorus available phosphorus, total potassium, and pH by 7.21%, 112.41%, 287.44%, 85.44% and 17.58%, respectively. The application of 10 t compost/ha resulted in the highest increase of soil total N by 44%.